Perfil sociodemográfico, clínico e cognitivo de idosos atendidos em um centro de referência, São Luís-MA - Martins, Maria de Fátima Carvalhal (2015)
Introduction: With population aging the prevalence in chronic degenerative disease, functional and cognitive deficits increased, leading to a paradigm shift in public health. Objective: Define the clinical and cognitive profile of an elderly population that seeks a referral center in São Luís - MA. Method: It is a descriptive cross-sectional study with 102 elderly. A questionnaire with sociodemographic variables, clinical morbidities and self-assessed health were used. For identification of cognitive impairment three tests were applied: MMSE - Mini-Mental State Examination, TDR-Clock Drawing Test and Verbal Fluency Test. For data analysis was used the 12ª version of SATA. Results: The prevalence of cognitive impairment was 60,7% when applied the MMSE, 23,5% for the test of verbal fluency and 59,8% to the TDR. When assessed the presence of cognitive deficit in only one of the tests, a total of 83, 3% was obtained and in the combination of the three tests were 16.6%. The majority of the elderly were female (72,5%), aged 60-64 years (33,3%), married / common-law marriage (43,1%), mulatto (52,9%), low education (66,6%), retired (66,6%) and family income at or below two minimum wages, living with family (41,1%). Hypertension was the most reported morbidity (56,8%), followed by osteoarticular diseases (52,9%) and diabetes (24,5%). Among others mentioned were dyslipidemia (20,5%), cerebrovascular accident (13,7%) and depression (10,7%). Seniors who reported no physical exercise were 77,4%. Conclusion: Cognitive impairment was present in the majority of the elderly. Arterial hypertension was the most frequent comorbidity followed by osteoarticular. With an aging population it is necessary intervention measures to identify early morbidity and cognitive impairment in an attempt to reduce or delay the functional and the autonomy loss.